Adaptation of Four Strawberry Varieties at a Land Altitude of 900 Meters ASL with Different Shade - Nugroho, Ary Susatyo; Sulistya Dewi, Endah Rita; Ulfah, Maria (Universitas PGRI Semarang, 2023)
Strawberries are herbaceous plants originating from sub-tropical regions. In Indonesia, which is a tropical climate, Strawberries can adapt well to the highlands of more than 1000 meters above sea level. At present, not much is known about strawberry varieties that are able to adapt to the plains below 1000 masl, so it is necessary to do research to find strawberry varieties that are able to adapt to the plains below 1000 masl. This research was conducted on agricultural land at an altitude of 900 masl in the Ngesrepbalong Village area, Limbangan District, Kendal Regency from September to October 2022. The research design used was a Completely Randomized Design with different types of shading. The treatment used is shading in the form of 50% paranet and 70% paranet. Data will be analyzed statistically with ANOVA and descriptive qualitative analysis. The results showed that the four strawberry varieties were able to adapt to an altitude of 900 meters above sea level with 50-70% paranet shade.